2020
DOI: 10.3390/ijms21030915
|View full text |Cite
|
Sign up to set email alerts
|

Phenylthiourea Binding to Human Tyrosinase-Related Protein 1

Abstract: Tyrosinase-related protein 1 (TYRP1) is one of the three human melanogenic enzymes involved in the biosynthesis of melanin, a pigment responsible for the color of the skin, hair, and eyes. It shares high sequence identity with tyrosinase, but has two zinc ions in its active site rather than two copper ions as in tyrosinase. Typical tyrosinase inhibitors do not directly coordinate to the zinc ions of TYRP1. Here, we show, from an X-ray crystal structure determination, that phenylthiourea, a highly potent tyrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…However, accurate identification of the residues is illusive as the protein is fixed during docking calculations. Docked positions are in accordance with a very recent publication where the X‐ray structure of TRP1‐phenylthiourea (PTU) adduct demonstrated that PTU pointed outward from the di‐metallic center [35] . Neither nitrogen atoms (amine or thioamide groups) or sulfur atoms interact with the dinuclear zinc center.…”
Section: Resultssupporting
confidence: 86%
“…However, accurate identification of the residues is illusive as the protein is fixed during docking calculations. Docked positions are in accordance with a very recent publication where the X‐ray structure of TRP1‐phenylthiourea (PTU) adduct demonstrated that PTU pointed outward from the di‐metallic center [35] . Neither nitrogen atoms (amine or thioamide groups) or sulfur atoms interact with the dinuclear zinc center.…”
Section: Resultssupporting
confidence: 86%
“…Tyrosinase is a key regulatory enzyme in the biosynthesis of melanin through melanogenesis, located in the membrane of melanosome with an internal, a transmembrane, and a cytoplasmic domain. , It is belonging to the family of metalloenzymes, known as copper-containing enzyme that catalyzes three distinct reactions of the melanogenic pathway: l -tyrosine hydroxylation and dehydrogenation of l -DOPA and DHI (5,6-dihydroxyindole). , Tyrosinase level is closely correlated with the malignancy level; hence, it became an important biomarker in the melanoma tumor. , Collectively, the tyrosinase enzyme is involved in several melanogenic pathways and hence it has become the most important target for melanogenesis inhibitors that are involving in direct inhibition of the tyrosinase catalytic activity . Phenyl­thiourea (PTU) is one of the most prominent and well-known tyrosinase inhibitors. , In recent years, compounds containing specific-enzyme inhibitors conjugated to chemotherapeutics, photosensitizers, etc. have gain much attention due to its increased targetability as well as therapeutic potency in the eradication of tumor.…”
Section: Introductionmentioning
confidence: 99%
“…These species finally polymerize to form eumelanin. In addition to the enzymatic activity, TRP1 is also a stabilizing protein for tyrosinase, as its role is still unclear depending on the metal cofactor found at the active site [14,15]. DHI as well DHICA can be oxidized in the absence of any enzyme to their respective o-quinones by oxygen and ROS generated during previous reactions [16].…”
Section: Natural Skin Pigments For Photoprotection: Melanin and Melanmentioning
confidence: 99%